THE CHALLENGES OF JUDICIALIZATION IN NEOCONSTITUTIONALISM AND THE PRINCIPLE OF SUSTAINABLE DEVELOPMENT (Revista Paradigma, 2020)
The research investigates the contribution of the Judiciary in Brazil, under the bias of neoconstitutionalism, in the search for implementation of the principle of sustainable development. From an analysis of the protagonism of the judiciary in relation to the other powers of the Republic, its possible benefits in the implementation of the Constitution and possible risks arising from possible excesses of judicial activism, we seek to evaluate judicial action in the motive of sustainable development. Possible conclusions point to a greater openness of the Judiciary Power to citizen participation and the replacement of mechanistic, individualistic and extractivist understandings, prevalent in the legal sciences, by a more systemic, holistic and humanistic right. Dialectical method and bibliographic research.